Liderazgo y clima organizacional en los colaboradores de la Municipalidad Distrital de Pebas 2022 - Panduro Navarro, Brigida Isabel (2024)
The study aimed to determine the relationship between leadership and organizational climate in the Municipalidad Distrital de Pebas. A quantitative, applied approach with a non-experimental, simple correlational design was adopted. The sample consisted of 100 employees from the Municipalidad Distrital de Pebas. Content-validated questionnaires with a Cronbach's Alpha of 0.922 were used. Data were processed using the SPSS V25 statistical program. The results showed a high level of correlation (76.1%) between leadership and organizational climate. It was concluded that there is a significant relationship between leadership and organizational climate in the Municipalidad Distrital de Pebas, with a Spearman correlation coefficient of 0.937, indicating a high positive correlation, with a significance level of p<0.05.